Isolation, identification, antimicrobial susceptibility test and public awareness of Salmonella on raw goat meat at Dire Dawa Municipal Abattoir, eastern Ethiopia - Ferede, B. (Addis Ababa University, 2014)
A cross-sectional study was conducted from January 2013 to April 2014 on 249 apparently healthy slaughtered goats at municipal abattoir of Dire Dawa. Since there is no report on the status of Salmonella, the study was conducted with the objectives to isolate, identify, estimate the prevalence, to delineate the antimicrobial sensitivity and assess public awareness on Salmonella. A total of 249 goat carcass swab were systematically collected and examined for the presence of Salmonella following the standard techniques and procedures. Out of the total of 249 carcass swab samples, 44 (17.7%) were positive to Salmonella. Of all isolates, 43(97.7%) were multiple antimicrobial resistant and highest level of resistance was observed for tetracycline (100%), nitrofurans (100%), streptomycin (81.8%) and kanamycin (79.5%). However, all isolates were susceptible to ciprofloxacin. The knowledge, attitude and practices of goat meat handlers and consumers and provided to the consumers were found poor. Therefore, goat meat provided to the city was found less hygienic and not safe for human consumption. Thus, urgent intervention program is essential to minimize the risk associated with consumption of goat meat contaminated with Salmonella. Finally, the authors recommended that the use of standardized procedures in slaughtering and handling of goat meat, provision of training on best practice of handling of meat for handlers and raising the level of awareness of people.